Communication techniques for disease prevention and control - Catalán-Matamoros, D.; Muñoz-Cruzado y Barba, M.; Fuentes Hervías, M.T. (Revista Española de Comunicación en Salud, 2016)
Communication could highly influence to the health of the population. In Primary Health Care (PHC), communication get an essential character due to that it is neccesary in developing most of these health level purposes, like disease prevention and health promotion. The types of communication are the verbal and non-verbal, being the last one more active in the process of communication. Our body, tone, pauses, laughs, etc. are important non-verbal elements in the process of interpersonal communication with the patient. Regarding to mass communication, the right use of print media and mass media may help the health professional in PHC to develope health campaigns addressed to the general population. The characteristics of every process of communication to ensure quality are defined. Some situations are showed in PHC where the use of communication becomes neccesary giving counselling and steps to follow. Health communication is a key tool in the PHC professional work. The use of effective communication would increase the health results, especially in health promotion and disease prevention. More training for health professionals in communication techniques is needed.